Removal of volatile gasoline compounds by indoor potted plants studied by pixel-based fingerprinting analysis. (April 2019) - Dela Cruz, Majbrit; Tomasi, Giorgio; Müller, Renate; Christensen, Jan H.
Abstract: Indoor potted plants are able to remove volatile organic compounds (VOC) from air, but only few studies have investigated the removal of compounds in mixtures. Here, we present a non-targeted pixel-based fingerprinting analysis documenting the removal of a complex mixture of gasoline VOCs by Hedera helix under dynamic chamber conditions allowing for air exchange and continuous gasoline exposure. For 15 days, the entire potted plant was exposed to gasoline; subsequently, the epigeous plant parts were removed and the soil microcosm (i.e. soil, plant roots and microorganisms) was exposed to gasoline for another eight days. Quantitative analysis was performed for heptane, 3-methylhexane, toluene, ethylbenzene and m, p-xylenes, and the CHEMSIC method (CHEMometric analysis of Selected Ion Chromatograms) was used for non-targeted pixel-based fingerprinting analysis. The quantitative analysis demonstrated that the presence of potted plants or pots without epigeous plant parts led to a reduction of selected VOCs by 16.7–22.6%. The CHEMSIC method confirmed this and revealed that all gasoline VOCs were reduced in concentration when H . helix was present. The estimate for the total VOC removal was in the range of 11–32%. The removal was highest for samples where the epigeous plant parts were absent and compounds known to be hard to degrade by microorganisms such as dimethylcyclopentanes were removed the least compared to compounds more easily degraded by microorganisms such as heptane when epigeous plant parts were removed. All findings support the conclusion that the soil microcosm was the main responsible for the removal of VOCs. Highlights: Potted Hedera helix was exposed to gasoline under dynamic conditions. Data was analyzed by a non-targeted pixel-based fingerprinting approach. All gasoline VOCs were reduced in concentration by H. helix . Preferential removal of some compounds was observed. The soil microcosm play a substantial role in removal of gasoline VOCs.